2012
DOI: 10.1155/2012/683872
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid Attenuates Platelet Activation and Platelet-Leukocyte Aggregation: Involving Pathways of Akt and GSK3β

Abstract: Platelet activation and its interaction with leukocytes play an important role in atherothrombosis. Cardiovascular diseases resulted from atherothrombosis remain the major causes of death worldwide. Gallic acid, a major constituent of red wine and tea, has been believed to have properties of cardiovascular protection, which is likely to be related to its antioxidant effects. Nonetheless, there were few and inconsistent data regarding the effects of gallic acid on platelet function. Therefore, we design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…It has been reported that it might alter three important pathways for platelet function, such as COX-1, PKCα/p38MAPK, and AKT/GSK3β protein activation [11,15]. The variety of platelet signaling pathways altered by gallic acid might explain the potent inhibitory effect that ester Gal Asc exerts on platelet aggregation, despite the moderate antioxidant power and also the moderate effect on [Ca 2+ ] c (shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been reported that it might alter three important pathways for platelet function, such as COX-1, PKCα/p38MAPK, and AKT/GSK3β protein activation [11,15]. The variety of platelet signaling pathways altered by gallic acid might explain the potent inhibitory effect that ester Gal Asc exerts on platelet aggregation, despite the moderate antioxidant power and also the moderate effect on [Ca 2+ ] c (shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The effect of gallic acid on platelet function has been well characterized [11]. It has been reported that it might alter three important pathways for platelet function, such as COX-1, PKCα/p38MAPK, and AKT/GSK3β protein activation [11,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, pomegranate, a rich source of gallic acid and ellagic acid, has been demonstrated to have anti-inflammatory effects and to significantly decrease LDL cholesterol but significantly increase HDL cholesterol in obese and overweight subjects [46,76,79]. Nevertheless, Chang et al [80] have shown that gallic acid inhibits ADP-induced platelet aggregation by reducing intracellular Ca 2+ concentration, attenuating phosphorylation-based transduction pathways and reducing P-selectin secretion. Another study by Olas et al [81] found out that grape seed extracts (containing a mixture of polyphenols including gallic acid, falvan-3-ols, and proanthocyanins) inhibited thrombin-and thrombin receptor-activation peptide (TRAP)-induced platelet activation and PMP formation more than another polyphenol, resveratrol [81][82][83].…”
Section: Impact Of Polyphenols On Pmp Productionmentioning
confidence: 99%
“…Meanwhile, resveratrol inhibited collagen‐induced platelet aggregation by stimulating platelet NO production and reducing platelet ROS production, when present at physiologically relevant concentrations (0.1–1 μM) (Messina et al , ). Simple phenolic acids, such as gallic acid, also inhibit platelet aggregation and activation via inhibition of the phosphorylation of PKCα/p38 MAPK and Akt/GSK3β (Chang et al , ). Similar findings were obtained for hippuric acid, the predominant metabolite of some phenolic acids and polyphenols, which reduced platelet aggregation and P‐selectin/CD62P expression at 1–2 mM.…”
Section: Polyphenols As Pharmacological Agentsmentioning
confidence: 99%